2011
DOI: 10.1007/s00296-011-1979-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of soy protein on collagen-induced arthritis in rat

Abstract: To evaluate preventive and therapeutic effects of soy protein on collagen-induced arthritis rats. Sprague-Dawley rats immunized with bovine type II collagen emulsified in adjuvant and treated with soy protein (7 g/kg), dexamethasone (1 mg/kg), and casein (in control groups) by daily gavages feedings for 30 days. Score of arthritis recorded every day for each paws of animal. Tumor necrosis factor-alpha, interleukin6, leptin, and adiponectin were measured in serums. Treatment with soy protein resulted in signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Feeding of soy protein isolate to rodents (which presumably generates bioactive short peptides through intestinal digestion) has shown beneficial effects on experimentally induced arthritis [53] and genetically predisposed atherosclerosis [54], through the induction of protective anti-inflammatory effects. Soybean peptides such as VPY and others have shown promise in controlling cytokine/chemokines levels, reduction of oxidative stress, and reversal of the tissue damage observed in animal models of colitis, suggesting potential applications in treatment of inflammatory bowel diseases [55, 56].…”
Section: Bioactive Peptides On Inflammationmentioning
confidence: 99%
“…Feeding of soy protein isolate to rodents (which presumably generates bioactive short peptides through intestinal digestion) has shown beneficial effects on experimentally induced arthritis [53] and genetically predisposed atherosclerosis [54], through the induction of protective anti-inflammatory effects. Soybean peptides such as VPY and others have shown promise in controlling cytokine/chemokines levels, reduction of oxidative stress, and reversal of the tissue damage observed in animal models of colitis, suggesting potential applications in treatment of inflammatory bowel diseases [55, 56].…”
Section: Bioactive Peptides On Inflammationmentioning
confidence: 99%
“…RA is a chronic inflammation disease characterized by persistent joint synovitis, proliferation of the synovial cells, and destruction of the cartilage and bone in a symmetrical distribution . Multiple factors as mentioned before in the introduction are involved in the development of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of the isoflavone content in soy protein should therefore be considered before it is used as a therapeutic agent-e.g., for metabolic syndrome [44,47]. A recent report by Mohammad Shahi et al [48] has demonstrated that the administration of soy protein to Sprague-Dawley rats protects them from collagen-induced arthritis (CIA), an animal model of human rheumatoid arthritis (RA).…”
Section: Soy Protein and Isoflavonesmentioning
confidence: 98%